PENGARUH LAYANAN PESAN SINGKAT PENGINGAT TERHADAP KEPATUHAN KONSUMSI OBAT PASIEN DM TIPE 2 DI PUSKESMAS MELATI KABUPATEN KAPUAS - Yugo Susanto; Riza Alfian; Rinidha Riana; Ibna Rusmana (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Diabetes mellitus is a chronic disease characterized by hyperglycemia and glucose intolerance. Patients with DM in Indonesia ranks 4th largest with a prevalence of 8.6 % of the total population. Patient compliance in the treatment greatly affect the success of the therapy. The purpose of this study was to determine the level of adherence before and after administration of short message reminders, as well as knowing the adherence changes that occur in patients with type 2 diabetes at the Puskesmas Melati Kabupaten Kapuas. This esearch was conducted by quasi experimental design, with prospective data collection during the period from May to June 2016. The intervention was giving short message service reminder. Subjects who met the inclusion criteria as many as 15 patients. The primary data collection is done by filling the questionnaire adherence MMAS and secondary data obtained from medical observation sheet. The results showed that in the pre intervention average value (mean) adherence by 5.8 or are in the low adherence rate, in post intervention average value of 7.4 or adherence are moderate adherence rates, with the rate of change (Δ) adherence towards better at 1.6. It can be concluded that the adherence were lower before than after giving short message service reminder. There was improvement in the adherence to taking medicine after giving short message service reminder. The giving short message service reminder increased the adherence to take medicine effectively